Fixed Points for the \(G\)-Contraction on \(E\)-\(b\)-Metric Spaces with a Graph - Hooda, Rahul; Kamra, Mamta; Malik, Archana (Communications in Mathematics and Applications, 2021)
In this paper, we study fixed points for the \(G\)-contraction on \(E\)-\(b\)-Metric spaces endowed with a graph. The work in this paper should be seen as a generalization of [7].